Batailles professionnelles et enjeux politiques - Éric Gobe; Wafa Khlif (Revue des Mondes Musulmans et de la Méditerranée)
Competition between chartered public accountants and lawyers professions under the Ben Ali's regime shows that in authoritarian contexts, professional mechanisms and politics are closely intertwined. Tunisian government has mediated between different professional interests with the only aim to perpetuate its authoritarian regime. At first stand, the specific political power relations between different actors, i.e. government, bar, public accountants, etc., has participated in shaping professional jurisdictions perceived by lawyers as curtailed to the benefit of the accounting profession. By that time, lawyers were considered as a dangerous profession by the government. The Tunisia « revolution » has inverted the balance of power in favor of the bar who took advantage of the 2011 ousting of President Ben Ali to expand and consolidate its professional power.